Objetivos y resultados obtenidos en mejoramiento en habichuela en el Departamento de Antioquia (Colombia) - Girard, E. (International Center for Tropical Agriculture, 1987)
In 1983, the vegetable dept. of the Instituto Colombiano Agropecuario (Colombia) started selection and crossing activities with 52 and 162 snap bean materials of determinate and indeterminate growth resp., obtained from commercial seed and the CIAT germplasm bank. In 1987, 3 determinate growth materials, with good general behavior, were selected and are being multiplied for regional trials in different growing areas. Seventeen indeterminate growth lines from F8 generation are currently being evaluated in the field; 4-5 stable lines are hoped to be selected in 1987. (CIAT)